Implementation of the Merdeka Curriculum in Elementary Schools: A Case Study at Padma Jaya Elementary School, Palembang: Implementing the Merdeka Curriculum in Elementary Schools: A Case Study in Indonesia - Nina Purwadinata; Sindi Aulia; Ginanda Ginanda; Jessycha Jessycha; Arcvita Arcvita; Anggun Anggun (Creative Smart Visionary, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum at the elementary school level through a case study approach at Padma Jaya Elementary School, Palembang. The focus of the study includes lesson planning, instructional practices, assessment, and the role of the school environment in supporting curriculum implementation. This study employs a qualitative approach with a case study design. Data were collected through observations and semi-structured interviews with the principal, vice principal, and classroom teachers. Data analysis was conducted using a thematic model that includes data display, data reduction, interpretation, and conclusion drawing. The analysis was strengthened through source and method triangulation. The findings indicate that the implementation of the Merdeka Curriculum has been carried out systematically. In the planning stage, teachers developed flexible and contextual teaching modules that align with students’ needs and integrated the Pancasila Student Profile Strengthening Project. In the implementation stage, learning activities were student-centered and active, using various methods such as discussions, hands-on activities, and project-based learning. Assessment was conducted authentically by covering attitudes, skills, and knowledge, and was followed by remedial and enrichment activities. In addition, support from the school environment, including facilities and collaboration among stakeholders, contributed to the effectiveness of curriculum implementation. The findings also reveal a strong alignment between planning, implementation, and assessment in supporting the success of the Merdeka Curriculum. This study provides empirical contributions to understanding contextual curriculum implementation practices at the elementary school level and may serve as a reference for improving educational policy and instructional practices.